2000
DOI: 10.1038/sj.cgt.7700150
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of drug cytotoxicity by reintroduction of wild-type p53 gene (Ad5CMV-p53) in human pancreatic cancer

Abstract: Chemotherapy does not significantly improve prognosis in pancreatic cancer. New therapeutical approaches involving p53 gene replacement appear to be very encouraging due to the key role of p53 in the cell response to DNA damage. Here, we have evaluated the effectiveness of combining wild-type p53 (wt-p53) gene reintroduction (Ad5CMV-p53) and exposure to two genotoxic drugs, gemcitabine and cisplatin, in several human pancreatic cell lines. The efficiency of the combinations was clearly dependent upon timing, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
34
1

Year Published

2001
2001
2010
2010

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 28 publications
5
34
1
Order By: Relevance
“…Moreover, other authors have reported that transfection of p53-null cells with wt-p53 expression vector enhanced the sensitivity of the cells to gemcitabine. 19,31 Conversely Merlin, 32 as well as Rieger, 33 have suggested that gemcitabine cytotoxicity does not require wt-p53 activity because they found no difference in the susceptibility to gemcitabine between cell lines with wt-p53 and cell lines with mutant or deleted p53. It is also possible that there are tissue-specific differences in the relationship between p53 status and sensitivity to gemcitabine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, other authors have reported that transfection of p53-null cells with wt-p53 expression vector enhanced the sensitivity of the cells to gemcitabine. 19,31 Conversely Merlin, 32 as well as Rieger, 33 have suggested that gemcitabine cytotoxicity does not require wt-p53 activity because they found no difference in the susceptibility to gemcitabine between cell lines with wt-p53 and cell lines with mutant or deleted p53. It is also possible that there are tissue-specific differences in the relationship between p53 status and sensitivity to gemcitabine.…”
Section: Discussionmentioning
confidence: 99%
“…17 Finally, alterations of apoptosis-regulating genes such as p53 also appear to be involved in the sensitivity of tumor cells to the cytotoxic effect of gemcitabine. 18,19 The effect of p53 status on sensitivity of cancer cells to chemotherapeutic agents depends on the dual role of p53 protein as a guardian of genome integrity and as a key intermediate of apoptosis. 20 p53 is markedly upregulated after DNA damage and blocks the cell cycle at the G1/S checkpoint or leads to apoptosis of the damaged cells.…”
mentioning
confidence: 99%
“…Recent reports demonstrated that p53 missense mutants markedly reduced DNA binding of wild-type p53 Previous reports have demonstrated that the combination of adenoviral p53 and cisplatin was cooperative in ovarian, breast, lung, pancreatic, prostate, head and neck cancer cells expressing mutant p53. [10][11][12][26][27][28] Furthermore adenoviral p53 might enhance the effect of taxanes in lung and ovarian cancer. 9,10,12,29 Although it appears that p53 is not involved in paclitaxel-dependent apoptosis, 30 it may enhance adenoviral transduction efficiency.…”
Section: Discussionmentioning
confidence: 99%
“…p53 gene mutations occur even more frequently in recurrent ovarian cancer and may affect response to chemotherapy. 8 Gene transfer of a wild-type p53 gene is intended to reverse the loss of normal p53 function and has been demonstrated to reduce proliferation of tumor cells alone or in combination with chemotherapy in vitro and in vivo among different types of tumors, such as breast, 9,10 head and neck, 9,10 prostate, 9,10 pancreas, 11 lung, 12 as well as ovarian cancer. 9,10,13,14 At least three major issues remain unclear when this therapeutic strategy is applied to ovarian cancer: the efficiency of the adenoviral transduction in ovarian cancer cells, the effect of adenoviral p53 on tumor cells with endogenous wild-type p53, the efficacy of the combination of current standard paclitaxel/carboplatin chemotherapy with adenoviral p53 gene transfer, systematically analyzed with regard to the mutational status.…”
mentioning
confidence: 99%
“…At 2 days after virus administration, X -gal staining showed that the expression of -galactosidase was restricted to patches of -gal -expressing cells around the injection points in the tumors. 44 No more than 20% of reduction in tumor growth was observed in animals treated with Ad -lacZ at the same dose as for Ad -p16 (data not shown ).…”
Section: Experiments In Vivomentioning
confidence: 88%